Analisis Pelaksanaan Strategi Pelayanan Provider Initiated HIV Testing And Counseling / PITC (Studi Kasus Di Balai Kesehatan Paru Masyarakat Semarang) - Sary, Lolita (Jurnal Promosi Kesehatan Indonesia, 2009)
Background: In Indonesia, there were 40% of AIDS fatality associated with tuberculosis. Mortality rate of TB-HIV co-infection were found four time higher compared to those who only suffer from tuberculosis. Voluntary Counseling and Testing is an important entrance of TB patients to obtain HIV services. This study aims to analyze the need assessment in establishing Provider Initiative HIV Testing and Counseling (PITC) Service in Semarang Lung Clinic.Method: alitative study involving health providers in Semarang Lung Clinic who were selected purposively. In-depth interviews were conducted to obtain qualitative data.Result: All respondents considering the establishment of Provider Initiative HIV Testing and Counseling (PITC) Service in Semarang Lung Clinic is necessary. Respondents’ knowledge of PITC service was quite good. Respondents’ motivation to be involved in PITC service was to shift patients’ perception of HIV infection and the availability incentive. Subjects hoped there will be numbers of additional counselors, case managers, and lab technician. They also require counseling room, case manager’s room, and data storages’ room. It is necessary to provide adequate information and socialization about TB-HIV and PITC, implementing TB-HIV service in Semarang Lung Clinic, adding TB-HIV counselors and team as well as tools and facilities.Keywords: Need assessment, PITC, Semarang, Lung, Clinic,TB-HIV